Ethnopharmaceutical Study of Medicinal Plants in Sumbersuko District, Lumajang Regency - Seran, Ivan Charles S Klau Charles; Utami, Wahyu Putri; Ningsih, Arista Wahyu; Rahmawati, Dewi; Fevi, Bella; Ambari, Yani (LPPM Akafarma Sunan Giri Ponorogo, 2025)
There are approximately 400 distinct ethnic groups in Indonesia (ethnic and sub-ethnic). Traditional medical practices are one example of the kinds of knowledge that have been handed down from one generation to the next in every nation, tribe, and subgroup within those nations. The people who live in the Lumajang Regency continue to have faith in the efficacy of traditional medicine. The practice of traditional medicine or shamans who treat residents around their residences in a number of districts in Lumajang, one of which is the Sumbersuko district, is evidence that this is the case. In the Sumbersuko District, there are a total of eight speakers who continue to uphold traditions related to the use of natural materials in medical practice. Interviews and questionnaires are being used as tools for the descriptive methodology that underpins this research project. According to the findings of this research, there are 37 different species of plants that are used as traditional medicine by the local community in the Sumbersuko District. These plants are categorized into 26 different families, with the Zingiberaceae family containing the most types of plants, including as many as 5 different species of plants. According to the findings of this research, the members of the community in the Sumbersuko District utilize the following plant parts: leaves, rhizomes, bulbs, fruits, skin, seeds, stems, flowers, sap, and all other plant parts. The leaf is the most commonly used component of the plant. To prepare plants for use, they are typically boiled, grated, ground, kneaded, and squeezed before being put to direct use.Keywords: consist of 3-5 words or phrases represent the focus of writing.